A karst rather than periglacial origin for small enclosed depressions of the Landes Triangle, southwest France - Bussière, Léa; Schmutz, Myriam; Dupuy, Alain (Earth surface processes and landforms, 2025)
Small topographic depressions offer insight into past and present groundwater recharge processes. The Landes Triangle (SW France) is dotted with over 2,400 such depressions, whose origins and hydrogeological implications remain unclear. This paper aims to disentangle their origin, with emphasis on the Villagrains-Landiras anticline sector: a key recharge zone, which also features the highest density of depressions. We first evaluate three historical hypotheses with open GIS data at the regional scale, then detail the near-surface structure of a depression near the anticline with electrical resistivity tomographies and ground-penetrating radar. We identify two groups of depressions based on their morphology, distribution and geological context. One aligns with an aeolian origin. The other (encompassing 97% of the depressions near the anticline) suggests a karst origin, with more circular shapes and proximity to karst, streams, faults and neighbouring depressions. However, 18% of these lie outside the crypto-karst area derived from GIS references and may rather be of periglacial origin. Yet, our geophysical survey revealed subsidence but no evidence of cryogenic sediment or solifluction. We conclude that a karst origin remains the best hypothesis in the anticline area, and highlight that sole reliance on GIS references may underestimate crypto-karst extent. Further geological investigation is therefore needed to map its full extent and related water pathways near the anticline.